The DOUBLETIME protein kinase regulates phosphorylation of the Drosophila PDP1epsilon. - Choi, C.; Lee, J.; Lim, C.; Jang, D.; Choe, J. (Journal of Neurochemistry, 2009)
Reversible phosphorylation of clock proteins plays an important role in circadian timekeeping as it is a key post-translational mechanism that regulates the activity, stability and subcellular localization of core clock proteins. The kinase DOUBLETIME (DBT), a Drosophila ortholog of mammalian casein kinase Iepsilon, regulates circadian phosphorylation of two essential clock proteins, PERIOD and dCLOCK. We present evidence that Par Domain Protein 1epsilon (PDP1epsilon), a transcription factor and mediator of clock output in Drosophila, is phosphorylated in vivo and in cultured cells by DBT activity. We also demonstrate that DBT interacts with PDP1epsilon and promotes its degradation by the ubiquitin-proteasome pathway in cultured cells. In addition, PDP1epsilon nuclear localization is decreased by dbt RNA interference in S2 cell system. These results suggest that DBT regulates phosphorylation, stability and localization of PDP1epsilon, and that it has multiple targets in the Drosophila circadian system.